2012
DOI: 10.1371/journal.pgen.1002789
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Evolutionary Changes in Regulatory Element Activity during Human Origins Are Associated with Altered Gene Expression and Positive Selection

Abstract: Understanding the molecular basis for phenotypic differences between humans and other primates remains an outstanding challenge. Mutations in non-coding regulatory DNA that alter gene expression have been hypothesized as a key driver of these phenotypic differences. This has been supported by differential gene expression analyses in general, but not by the identification of specific regulatory elements responsible for changes in transcription and phenotype. To identify the genetic source of regulatory differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
143
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 126 publications
(159 citation statements)
references
References 70 publications
15
143
1
Order By: Relevance
“…This hypothesis is consistent with experimental results confirming a role for AP-1 in diverse pathways (Angel and Hess 2012). Recent evidence also corroborates the general role of AP-1 in forming accessible chromatin; for example, Shibata et al (2012) found AP-1 motifs to be associated with chromatin accessibility differences among primates. Similarly, Biddie et al (2011) showed that inhibiting AP-1 impedes formation of accessible chromatin and reduces glucocorticoid receptor (GR) binding, suggesting that AP-1 has a role in transcriptional pathways mediated by GR.…”
Section: Discussionsupporting
confidence: 88%
“…This hypothesis is consistent with experimental results confirming a role for AP-1 in diverse pathways (Angel and Hess 2012). Recent evidence also corroborates the general role of AP-1 in forming accessible chromatin; for example, Shibata et al (2012) found AP-1 motifs to be associated with chromatin accessibility differences among primates. Similarly, Biddie et al (2011) showed that inhibiting AP-1 impedes formation of accessible chromatin and reduces glucocorticoid receptor (GR) binding, suggesting that AP-1 has a role in transcriptional pathways mediated by GR.…”
Section: Discussionsupporting
confidence: 88%
“…For example, the DHSs we used were ascertained only in human tissues. Although experimentally defined regulatory DNA has been generated in a limited number of nonhuman primates for a limited number of tissues (Shibata et al 2012;Cotney et al 2013), a more systematic and comprehensive effort would be of considerable value in understanding the evolution of regulatory sequences. Furthermore, we did not consider additional types of genetic variation, such as structural variation, that may influence humanspecific phenotypes (Dennis et al 2012;Sudmant et al 2013).…”
Section: Wwwgenomeorgmentioning
confidence: 99%
“…Dynamic changes in transcription across tissues and developmental stages or in response to environmental challenges can be particularly informative (e.g., Jiménez-Gómez et al 2010, Hammond et al 2011, Hines et al 2012, Yuan et al 2012. Assays for other kinds of molecular functions are beginning to find their way into evolutionary studies, including alternative splicing (e.g., Barbosa-Morais et al 2012, Merkin et al 2012, histone modification (e.g., Cain et al 2011), DNA methylation (e.g., Pai et al 2011) and chromatin configuration (e.g., Degner et al 2012, Shibata et al 2012). …”
Section: Functional Genomic Approachesmentioning
confidence: 99%